2015
DOI: 10.1002/adfm.201502669
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Detectors Based on Solution‐Grown Organic Single Crystals

Abstract: Organic single crystals (OSCs) have ideal qualities (well defi ned structure and\ud morphology, lack of grain boundaries, high purity, 3D long range order, good\ud electronic transport properties) for several technological applications, in particular\ud as key components for electronic devices. It is only recently that OSCs\ud have been considered as ionizing radiation detectors, and the latest developments\ud in this fi eld are here reported. In the fi rst section, various methods for\ud OSC growth are descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 96 publications
(141 reference statements)
1
49
0
1
Order By: Relevance
“…Second, these two materials were grown easier transport for triplets easier transport for triplets after some transport initial distribution with melt-growth techniques, while the others were grown with solution processing. While it has been demonstrated that PSD performance can be significantly degraded in melt-grown crystals [1], previous anisotropy measurements demonstrated that the anisotropy effect is roughly the same between meltgrown and solution-grown stilbene [19]. Thus, the effect of imperfections in the crystal structure that result in melt-grown crystals on the anisotropy effect does not appear to be strong.…”
Section: Relationship To Crystal Structurementioning
confidence: 93%
See 1 more Smart Citation
“…Second, these two materials were grown easier transport for triplets easier transport for triplets after some transport initial distribution with melt-growth techniques, while the others were grown with solution processing. While it has been demonstrated that PSD performance can be significantly degraded in melt-grown crystals [1], previous anisotropy measurements demonstrated that the anisotropy effect is roughly the same between meltgrown and solution-grown stilbene [19]. Thus, the effect of imperfections in the crystal structure that result in melt-grown crystals on the anisotropy effect does not appear to be strong.…”
Section: Relationship To Crystal Structurementioning
confidence: 93%
“…Their rich hydrogen content makes it possible to detect both fast neutrons and gamma-rays, between which they can discriminate using pulse shape discrimination (PSD). While these materials have been available for decades, recent advancements in methods for growing organic single crystals from solution processing have produced large-scale crystalline materials (on the order of 10 cm in each dimension) with superior scintillation properties [1,2], igniting renewed interest in their use.…”
mentioning
confidence: 99%
“…), the special advantages of high purity,l ow fabrication cost, and high hydrogen content in organic single crystals makes them suitable for the detection of ionizing radiation. [131] Twod etection mechanisms have been reported:indirect detection and direct detection. In the former detection mode,the ionizing radiation is changed into an electrical signal according to atwo-step exchange process: from radiation to avisible photon via ascintillator, and then, from the photon to an electrical output via ap hotodiode.…”
Section: Organic Single-crystal Detectorsmentioning
confidence: 99%
“…However, the cost involved in depositing these materials for electronic applications in addition to the small size limits (typically of the order of 0.5-1 mm) makes such growth methods impractical for upscaling to industrially relevant fabrication. An alternative to vapor deposition is a solution-based growth method, which has the substantial advantage of compatibility with large-scale printing fabrication, as it provides a solution-processable OSC ink [189]. Initial attempts to create solution-based OSC crystals involved the slow evaporation of solvent from solutions containing dissolved OSC materials using heat and light.…”
Section: Organic Semiconducting Molecular Crystalsmentioning
confidence: 99%
“…Examples of successful deployment of large-area OSC molecular crystal scintillators include diphenylethylene (stilbene) [194], 9,10diphenylanthracene (DPA) [195], naphthalene, and anthracene [196]. These solution-grown OSC crystals have a series of unique features (and limitations) that will not be described in detail here but have been outlined extensively in a recent review [189].…”
Section: Organic Semiconducting Molecular Crystalsmentioning
confidence: 99%